Lakes of grass - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Bourgou grass (Echinochloa stagnina), which is useful for grazing and conserved forage, has been regenerated on over 4,000 hectares of flood plains in the Inner Delta of Mali. As a result, farmers have been able to increase their incomes through...